2019
DOI: 10.1038/s41419-019-1746-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective role of APIP in myocardial infarction through ADORA2B

Abstract: In ischemic human hearts, the induction of adenosine receptor A2B (ADORA2B) is associated with cardioprotection against ischemic heart damage, but the mechanism underlying this association remains unclear. Apaf-1-interacting protein ( APIP) and ADORA2B transcript levels in human hearts are substantially higher in patients with heart failure than in controls. Interestingly, the APIP and ADORA2B mRNA levels are highly cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The APAF-1 inhibitor attenuated cardiomyocyte apoptosis via disturbing procaspase-9 recruitment by APAF-1 [ 15 ]. Moreover, APAF-1-interacting protein plays cardioprotective roles in myocardial infarction [ 35 ]. Subsequently, APAF1 inhibitor ZYZ-488 was used to further validate whether APAF-1/Caspase9 signaling pathway mediated the cardioprotective role of APPL1 in I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…The APAF-1 inhibitor attenuated cardiomyocyte apoptosis via disturbing procaspase-9 recruitment by APAF-1 [ 15 ]. Moreover, APAF-1-interacting protein plays cardioprotective roles in myocardial infarction [ 35 ]. Subsequently, APAF1 inhibitor ZYZ-488 was used to further validate whether APAF-1/Caspase9 signaling pathway mediated the cardioprotective role of APPL1 in I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…When looking at genes that showed differential imbalance between the autoimmunity related phenogroup 2 and the rest of the cohort, four out of the top five most significant hits were related to inflammatory processes like programmed cell death and autophagy (Supplementary Table 2) [20][21][22][23] . One of these genes, APIP, has been shown to carry out a cardioprotective role in the inflammatory process following myocardial infarction 20 . TFEB is a protein degradation promotor previously linked to autophagy and lysosomal related cardiac disorders 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is conceivable that in many cases the predominant A 2B AR coupling is through Gαi rather than Gαs. Many important A 2B AR functions from primary cells or tissues have recently been related to the PI3K-Akt and Ras-related protein (RAP)1B-EPAC pathways [59,60,61,62,63]. However, it has not been extensively explored whether those signaling molecules are actually downstream of A 2B AR-mediated Gαi or Gαs proteins.…”
Section: A2bar Signalingmentioning
confidence: 99%
“…The cAMP-EPAC pathway and ERK1/2 phosphorylation are known to be involved in A 2B AR-mediated proliferation of some endothelial cells [55,83]. Limm et al, [61] showed that PKC, but not cAMP or Ca 2+ , is involved in 5′-methylthioadenosine (2)-induced and A 2B AR-mediated melanoma cell proliferation. Forskolin can mimic adenosine-induced proliferation of MDA-MB-231 breast cancer cells, suggesting that Gs-cAMP signaling is involved, although it is not clear whether PKA or EPAC is the downstream mediator.…”
Section: A2bar In Cell Proliferation and Tumor Growthmentioning
confidence: 99%